Synthesis process of polysiloxane resin with low refractive index

By directly reacting amino bi-terminated polydimethylsiloxane and isocyanate under an inert gas atmosphere, the complex problem of using organic solvents in the prior art is solved, and the synthesis of low-refractive index polysiloxane resins is achieved under solvent-free conditions , simplify the process and improve product performance.

CN119490637AActive Publication Date: 2025-02-21CHANGDI NEW MATERIAL TECHNOLOGY (SHANGHAI) CO LTD

Patent Information

Application Number
CN202510083517.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-02-21
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing low-refractive index polysiloxane resin modification process requires the use of organic solvents, which leads to complex production process and the product needs to be post-treated to remove solvents, affecting process efficiency and product performance.

Method used

The amino bi-terminated polydimethylsiloxane and isocyanate are used as the main raw materials, and the reaction is directly carried out under an inert gas atmosphere to obtain a low-refractive index polysiloxane resin. The product can be directly used in multi-layer optical films without the use of organic solvents. Production.

Benefits of technology

The low-refractive index resin is achieved in a step of synthesis under solvent-free conditions, simplifying the process flow, reducing the energy consumption of solvent treatment, and the product's refractive index is 1.41~1.44, and has excellent elastic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of optical resin, and particularly discloses a synthesis process of polysiloxane resin with a low refractive index. The synthesis process comprises the following steps: taking amino double-terminated polydimethylsiloxane and isocyanate as main raw materials, feeding the amino double-terminated polydimethylsiloxane and the isocyanate according to a molar ratio of 1: (1-2), and reacting in an inert gas atmosphere to obtain the low-refractive-index polysiloxane resin. A target product can be obtained through direct reaction in a solvent-free state, the refractive index of the target product is controlled to be 1.41-1.44, the elongation at break can reach 200-400%, and the target product has excellent elasticity; the target product can be directly subjected to subsequent melt extrusion, is more environment-friendly compared with a solvent method, and is more suitable for manufacturing an elastomer multilayer optical film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of optical resins, and more specifically, to a synthesis process of low-refractive-index polysiloxane resins. Background Art

[0002] Multilayer polymer optical films have the characteristics of high reflectivity, high transmittance and light weight, and can be widely used in liquid crystal displays, solar cells, lasers and other fields. Multilayer polymer optical films mainly use the principle of optical interference to alternately stack materials with different refractive indices through a dispenser according to a predetermined design plan, suppress reflected light and enhance transmitted light, so that the optical film has higher transparency and color reproduction.

[0003] By increasing the refractive index difference between the resin materials used in the two adjacent layers of the optical film, the optical power, thickness, reflection bandwidth and other aspects of the optical film can be improved. However, the low refractive index materials currently used in optical films are mainly polymethyl methacrylate (refractive index of 1.49) and polyethylene (refractive index of 1.50). The development of low refractive index materials is of great value, and the refractive index of resin materials still needs to be reduced.

[0004] Due to the physical and chemical properties of the siloxane bond, polysiloxane elastomers have good UV resistance and oxidation stability. At present, the industry's research on improving the refractive index of polysiloxane elastomers is as follows: The patent with application number CN201780034603.5 modifies polysiloxane elastomer with fluorine-containing monomers, and uses silane monomers containing chlorosilane functional groups, silane monomers containing at least one fluoroalkyl group, silane monomers containing (meth)acryloyl functional groups, ether monomers and silicone resins as the main reaction raw materials to synthesize highly fluorinated silicone resins. Although the refractive index of the resin can be reduced to below 1.4, the resin is expensive, and the increased degree of fluorination affects its compatibility with other resins, and the problem of weak interface bonding is prone to occur during co-extrusion.

[0005] The patent with application number CN202211647789.0 modifies hydroxyalkyl silane monomers and polysiloxane in organic solvents. The resin can be coated on the surface of the substrate by roller coating, dip coating, inkjet and other methods, and cured by thermal curing. The resin needs to be used with organic solvents, and there is currently no relevant method to show that it can be used for lamination and extrusion with other resins; even if it can be extruded, it still needs to remove the organic solvent before subsequent distribution and lamination steps can be carried out.

[0006] Based on the above situation, the current modification and preparation methods for low refractive index polysiloxane elastomers all need to be carried out in the presence of organic solvents, and the products produced need to be post-treated before melt co-extrusion. Summary of the invention

[0007] In order to solve the problem that organic solvents are required for the modification of existing polysiloxane resins, the present application provides a low-refractive-index polysiloxane resin synthesis process, which can synthesize low-refractive-index resins in one step without solvents, and the resin particles can be directly used in the production of elastomeric multilayer optical films.

[0008] The present application provides a low refractive index polysiloxane resin synthesis process, which adopts the following technical solution: A low refractive index polysiloxane resin comprises the following steps: Amino di-terminated polydimethylsiloxane and isocyanate are used as main raw materials, the amino di-terminated polydimethylsiloxane and isocyanate are added in a molar ratio of 1:(1-2), and reacted under an inert gas atmosphere to obtain a low refractive index polysiloxane resin.

[0009] Furthermore, the amino di-terminated polydimethylsiloxane is aminopropyl di-terminated polydimethylsiloxane.

[0010] Furthermore, the weight average molecular weight of the aminopropyl dicapped polydimethylsiloxane is 2000-10000.

[0011] Furthermore, the weight average molecular weight of the aminopropyl dicapped polydimethylsiloxane is 5,000.

[0012] Furthermore, the isocyanate is one or more of hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, phenyl isocyanate, and 4,4',4"-triphenylmethane triisocyanate.

[0013] Furthermore, the isocyanate is diisocyanate.

[0014] Furthermore, the diisocyanate is 4,4'-dicyclohexylmethane diisocyanate.

[0015] Furthermore, the amino di-terminated polydimethylsiloxane and isocyanate react in a molar ratio of 1:1.

[0016] Furthermore, the reaction temperature under the inert gas atmosphere is 0 to 210° C., and the insulation reaction time is 2 to 4 hours.

[0017] Furthermore, the reaction temperature under the inert gas atmosphere is 170-210° C., and the insulation reaction time is 2-4 hours.

[0018] Furthermore, the inert gas is selected from nitrogen or argon.

[0019] Furthermore, after the reaction is completed, the reaction product is dried at 80-95° C. for 2-6 hours.

[0020] By adopting the above technical solution, this application has at least the following advantages: First, in terms of process, the present application uses aminopropyl di-terminated polydimethylsiloxane and isocyanate as main raw materials, directly drops isocyanate into aminopropyl di-terminated polydimethylsiloxane, and directly reacts under the protection of inert gas. After drying, the reaction product can be directly put into the extruder for melt extrusion, without the need to remove a large amount of organic solvent, thus saving energy consumption for solvent treatment. The synthesis process is simple, the reaction temperature range is wide, the operation is controllable, and it is green and environmentally friendly.

[0021] Second, in terms of product performance, the target product obtained in this application has been tested with an Abbe refractometer (25°C) and a prism coupler (636nm). The test results show that the refractive index of the product is 1.41-1.44, which is a low refractive index. After mechanical properties testing, the elongation at break of the product can reach 200-400%, and it has excellent elasticity.

[0022] Third, in-depth research on the process of this application found that the weight average molecular weight of aminopropyl dicapped polydimethylsiloxane has a great influence on the refractive index and elongation at break of the resin. Within a specific weight average molecular weight range, a resin with a refractive index ≤ 1.4250 and an elongation at break ≥ 390% can be obtained. The functionality of isocyanate also has a certain influence on the refractive index and elongation at break of the resin. The reaction of diisocyanate with aminopropyl polydimethylsiloxane can balance the reduction of the refractive index and the increase of the elongation at break. DETAILED DESCRIPTION

[0023] The present application is further described in conjunction with the following examples, comparative examples and test data.

[0024] Aminopropyl double-terminated polydimethylsiloxane: a customized product with a weight-average molecular weight of 2000-10000; Hexamethylene diisocyanate, purity ≥98%; Isophorone diisocyanate, purity ≥98%; 4,4'-Dicyclohexylmethane diisocyanate, purity ≥98%; 4,4'-diphenylmethane diisocyanate, purity ≥98%; Phenyl isocyanate, purity ≥98%; 4,4',4"-Triphenylmethane triisocyanate, purity ≥98%.

[0025] Example 1

[0026] A low refractive index polysiloxane resin synthesis process is carried out according to the following steps: Weigh 50.06 g of aminopropyl di-terminated polydimethylsiloxane with a weight average molecular weight of 5000 into a three-necked flask, slowly add 2.62 g of 4,4'-dicyclohexylmethane diisocyanate, and introduce nitrogen at the same time. After the addition is completed, heat to 170°C under a nitrogen atmosphere, keep stirring and react at 200 rpm for 4 hours, pour out, and dry at 95°C for 4 hours to obtain the target product.

[0027] Example 2

[0028] A low refractive index polysiloxane resin synthesis process is carried out according to the following steps: Weigh 20.02 g of aminopropyl di-terminated polydimethylsiloxane with a weight average molecular weight of 2000 into a three-necked flask, slowly add 2.62 g of 4,4'-dicyclohexylmethane diisocyanate, and introduce nitrogen at the same time. After the addition is completed, heat to 170°C under a nitrogen atmosphere, keep stirring and react at 200 rpm for 4 hours, pour out, and dry at 95°C for 4 hours to obtain the target product.

[0029] Example 3

[0030] A low refractive index polysiloxane resin synthesis process is carried out according to the following steps: Weigh 100.11 g of aminopropyl di-terminated polydimethylsiloxane with a weight average molecular weight of 10,000 into a three-necked flask, slowly add 2.62 g of 4,4'-dicyclohexylmethane diisocyanate, and introduce nitrogen at the same time. After the addition is completed, heat to 170°C under a nitrogen atmosphere, keep stirring at 200 rpm for 4 hours, pour out, and dry at 95°C for 4 hours to obtain the target product.

[0031] The difference between Examples 1-3 is that the weight average molecular weights of aminopropyl diblocked polydimethylsiloxane are different. Three aminopropyl diblocked polydimethylsiloxanes with different weight average molecular weights are reacted with 4,4'-dicyclohexylmethane diisocyanate at a molar ratio of 1:1. The target products are tested by Abbe refractometer (25°C) and prism coupling instrument (636nm). The test results are as follows:

[0032] The test results show that: first, the test results of the Abbe refractometer and the prism coupler are not much different, indicating that the refractive index measurement value of the target product is accurate; second, the overall refractive index of the resin is low, and as the weight average molecular weight of aminopropyl dimethylsiloxane increases, the refractive index of the resin shows a downward trend; third, as the weight average molecular weight of aminopropyl dimethylsiloxane increases, the elongation at break of the resin shows a trend of first increasing and then decreasing. When the weight average molecular weight of aminopropyl dimethylsiloxane is 5000, the elongation at break reaches more than 390%.

[0033] Example 4

[0034] A low refractive index polysiloxane resin synthesis process is carried out according to the following steps: Weigh 50.04 g of aminopropyl di-terminated polydimethylsiloxane with a weight average molecular weight of 5000 into a three-necked flask, slowly add 1.19 g of phenyl isocyanate, and introduce nitrogen at the same time. After the addition is completed, heat to 170°C under a nitrogen atmosphere, keep stirring at 200 rpm for 4 hours, pour out, and dry at 95°C for 4 hours to obtain the target product.

[0035] Example 5

[0036] A low refractive index polysiloxane resin synthesis process is carried out according to the following steps: Weigh 50.31 g of aminopropyl di-terminated polydimethylsiloxane with a weight average molecular weight of 5000 into a three-necked flask, slowly add 3.67 g of 4,4',4"-triphenylmethane triisocyanate, and introduce nitrogen at the same time. After the addition is completed, heat to 170°C under a nitrogen atmosphere, keep stirring at 200 rpm for 4 hours, pour out, and dry at 95°C for 4 hours to obtain the target product.

[0037] Examples 1 and 4-5 form a single comparison. The difference lies in the different functionalities of the isocyanates. The three isocyanates with different functionalities react with aminopropyl di-terminated polydimethylsiloxane in a molar ratio of 1:1. The target product is tested by an Abbe refractometer (25°C) and a prism coupling instrument (636nm). The test results are as follows:

[0038] The test results show that: first, as the number of isocyanate groups increases, the functionality increases and the refractive index of the resin increases; second, as the functionality of the isocyanate increases, the elongation at break of the resin shows a trend of first increasing and then decreasing.

[0039] Example 6

[0040] A low refractive index polysiloxane resin synthesis process is carried out according to the following steps: Weigh 50.05 g of aminopropyl di-terminated polydimethylsiloxane with a weight average molecular weight of 5000 into a three-necked flask, slowly add 1.68 g of hexamethylene diisocyanate, and introduce nitrogen at the same time. After the addition is completed, heat to 170°C under a nitrogen atmosphere, keep stirring at 200 rpm for 4 hours, pour out, and dry at 95°C for 4 hours to obtain the target product.

[0041] Example 7

[0042] A low refractive index polysiloxane resin synthesis process is carried out according to the following steps: Weigh 50.12 g of aminopropyl di-terminated polydimethylsiloxane with a weight average molecular weight of 5000 into a three-necked flask, slowly add 2.23 g of isophorone diisocyanate, and introduce nitrogen at the same time. After the addition is completed, heat to 170°C under a nitrogen atmosphere, keep stirring at 200 rpm for 4 hours, pour out, and dry at 95°C for 4 hours to obtain the target product.

[0043] Example 8

[0044] A low refractive index polysiloxane resin synthesis process is carried out according to the following steps: Weigh 50.08 g of aminopropyl di-terminated polydimethylsiloxane with a weight average molecular weight of 5000 into a three-necked flask, slowly add 2.50 g of 4,4'-diphenylmethane diisocyanate, and introduce nitrogen at the same time. After the addition is completed, heat to 170°C under a nitrogen atmosphere, keep stirring and react at 200 rpm for 4 hours, pour out, and dry at 95°C for 4 hours to obtain the target product.

[0045] Examples 1 and 6-8 form a single comparison. The difference lies in the different types of diisocyanates, and their structures and molecular weights are different. Four different types of diisocyanates are reacted with aminopropyl di-terminated polydimethylsiloxane in a molar ratio of 1:1. The target products are tested by Abbe refractometer (25°C) and prism coupling instrument (636nm). The test results are as follows:

[0046] The test results show that: first, the structure of the isocyanate group has an effect on the refractive index of the resin. The introduction of methylene, methyl and other groups helps to reduce the refractive index of the resin. At the same time, the molecular weight and segment structure also have different effects on the refractive index of the resin; second, as the molecular weight of the diisocyanate gradually increases, the elongation at break of the resin also gradually increases. Taking all factors into consideration, the reaction of 4,4'-dicyclohexylmethane diisocyanate with aminopropyl dicapped polydimethylsiloxane can not only reduce the refractive index of the resin, but also significantly improve the elongation at break of the resin.

[0047] Example 9

[0048] A low refractive index polysiloxane resin synthesis process is carried out according to the following steps: Weigh 50.08 g of aminopropyl di-terminated polydimethylsiloxane with a weight average molecular weight of 5000 into a three-necked flask, slowly add 3.36 g of hexamethylene diisocyanate, and introduce nitrogen at the same time. After the addition is completed, heat to 170°C under a nitrogen atmosphere, keep stirring at 200 rpm for 4 hours, pour out, and dry at 80°C for 6 hours to obtain the target product.

[0049] Example 6 and Example 9 form a single comparison, and the difference is only in the molar ratio. The molar ratio in Example 6 is 1:1, and the molar ratio in Example 9 is 1:2. The target product is tested by an Abbe refractometer (25°C) and a prism coupler (636nm), and the test results are as follows:

[0050] The test results show that an increase in the molar ratio will simultaneously increase the resin's refractive index and elongation at break.

[0051] Examples 10-12 A low refractive index polysiloxane resin synthesis process, which differs from Example 1 in that the reaction temperature and other related parameters are different, as follows:

[0052] The target product was tested by Abbe refractometer (25°C) and prism coupling instrument (636nm), and the test results are as follows:

[0053] The test results show that the change of reaction temperature has little effect on the refractive index of the resin. The higher the reaction temperature, the more complete the reaction between the raw materials, which has a positive effect on improving the elongation at break of the resin.

[0054] Comparative Example 1 A low refractive index polysiloxane resin synthesis process is carried out according to the following steps: Weigh 50.03 g of aminopropyl di-terminated polydimethylsiloxane with a weight average molecular weight of 5000 into a three-necked flask, add 50.13 g of tetrahydrofuran, and stir. Weigh 2.62 g of 4,4'-dicyclohexylmethane diisocyanate, dissolve it in 2.62 g of tetrahydrofuran, and slowly add it dropwise to the three-necked flask. React at 25°C for 6 h, pour it out, and dry it at 95°C for 48 h to obtain the target product.

[0055] The target product was tested by Abbe refractometer (25°C) and prism coupling instrument (636nm), and the test results are as follows:

[0056] The test results show that: first, in comparative example 1, the solvent method is used for synthesis, and the weight ratio of the reaction material to the tetrahydrofuran solvent in the solvent method exceeds 1:1. The reaction time of the resin synthesized by the solvent method is longer, and the subsequent solvent treatment time is doubled; the target product after drying needs further heating or vacuum treatment to prevent the residual solvent from volatilizing after melt extrusion, resulting in unstable performance of the extruded optical film. Second, the elongation at break of the resin obtained in the solvent-free reaction is significantly improved.

[0057] Practical Application: The resin particles obtained in Example 1 and the extruded polyester TPU (model Covestro 88375A) were melted, and then transferred to the designed multi-layer feed block after passing through a melt metering pump and a filter screen. The resin particles obtained in Example 1 formed film layer I, and the extruded polyester TPU formed film layer II. The film layers I and II were alternately laminated according to the designed optical thickness. The laminated film was biaxially stretched to obtain an optical film 1. The resin particles obtained in Comparative Example 1 and the extruded polyester TPU (model Covestro 88375A) were melted, and then transferred to the designed multi-layer feed block after passing through a melt metering pump and a filter screen. The resin particles obtained in Comparative Example 1 formed film layer I, and the extruded polyester TPU formed film layer II. The film layers I and II were alternately laminated according to the designed optical thickness, and the laminated film was biaxially stretched to obtain an optical film 2; Optical film 1 and optical film 2 have the same number of laminated layers, the same single-layer optical thickness, the same stacking order, and the same parameters in the process such as biaxial stretching. The visible light transmittance and near-infrared reflectivity of the optical film were measured using a solar film tester LS162; the haze of the optical film was measured using a haze meter; the tensile strength and elongation at break of the optical film were measured using a universal testing machine, and the test results are as follows:

[0058] According to the above test results, it can be seen that the optical film 1 has low haze and high visible light transmittance, and the optical properties of the optical film 1 are excellent; at the same time, the optical film 1 has high tensile strength and high elongation at break, and the mechanical properties of the optical film 1 are also more excellent.

[0059] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0060] Moreover, the above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A process for synthesizing a low refractive index polysiloxane resin, characterized in that: The steps include: Amino di-terminated polydimethylsiloxane and isocyanate are used as main raw materials, the amino di-terminated polydimethylsiloxane and isocyanate are added in a molar ratio of 1:(1-2), and reacted under an inert gas atmosphere to obtain a low refractive index polysiloxane resin.

2. A process for synthesizing a low refractive index polysiloxane resin as claimed in claim 1, characterized in that: Amino bis-terminated polydimethylsiloxane is aminopropyl bis-terminated polydimethylsiloxane.

3. A process for synthesizing a low refractive index polysiloxane resin as claimed in claim 2, characterized in that: The weight average molecular weight of the aminopropyl double-terminated polydimethylsiloxane is 2000-10000.

4. A process for synthesizing a low refractive index polysiloxane resin as claimed in claim 3, characterized in that: The weight average molecular weight of the aminopropyl double-terminated polydimethylsiloxane is 5000.

5. A process for synthesizing a low refractive index polysiloxane resin as claimed in claim 1, characterized in that: The isocyanate is diisocyanate.

6. A process for synthesizing a low refractive index polysiloxane resin as claimed in claim 5, characterized in that: The diisocyanate is 4,4'-dicyclohexylmethane diisocyanate.

7. A process for synthesizing a low refractive index polysiloxane resin as claimed in claim 1, characterized in that: The amino di-terminated polydimethylsiloxane and isocyanate react in a molar ratio of 1:

1.

8. A process for synthesizing a low refractive index polysiloxane resin as claimed in claim 1, characterized in that: The reaction temperature under the inert gas atmosphere is 0-210° C., and the insulation reaction time is 2-4 hours.

9. A process for synthesizing a low refractive index polysiloxane resin as claimed in claim 8, characterized in that: The reaction temperature under the inert gas atmosphere is 170-210° C., and the insulation reaction time is 2-4 hours.

10. A process for synthesizing a low refractive index polysiloxane resin as claimed in claim 1, characterized in that: After the reaction is completed, the reaction product is dried at 80-95° C. for 2-6 hours.

Citation Information

Patent Citations

  • Reactive resins and formulations for low refractive index and low dielectric constant applications

    CN109219631A

  • Low refractive index optical resin

    CN118222176A

  • Crosslinkable siloxane urea copolymers

    CN101010361A

  • Slippery self-lubricating polymer surfaces

    CN104704067A

  • Self-repairing polysiloxane elastomer based on strong and weak hydrogen bond interaction and preparation method thereof

    CN115819776A

Cited By

  • Fluorine-containing polyester compound with low refractive index as well as preparation method and application of fluorine-containing polyester compound

    CN121362323A